Development and validation of a sunflower crop growth module for the Daisy model - Pouryazdankhah, Hedyeh; Shahnazari, Ali; Ahmadi, Mirkhalegh Z.; Khaledian, Mohammadreza; Andersen, Mathias N. (Frontiers in Sustainable Food Systems, 2024)
The objective of this study was to develop a crop model for sunflower in Daisy. For this intent, the field experiment data of two full irrigation treatments for 2 years, 2012 and 2013, were used to develop the crop model. The average RMSE of the dry matter (DM), leaf area index (LAI), height of plant (H), and water content parameters in the treatments utilized for calibration was calculated 0.093 Ton/ha, 0.198 cm2/cm2, 2.25 cm, and 1.035%, respectively. The average RMSE of the parameters of DM, LAI, H, and water content in the treatments utilized for validation were estimated 0.207 Ton/ha, 0.272 cm2/cm2, 4.22 cm, and 1.123%, respectively. The results of the validation showed that the developed crop model had good accuracy making it useful for simulation of sunflower agroecology. It is suggested to use the developed crop model in the information library of Daisy and survey and calibrate it for other areas with different climates and sunflower varieties.